Investigation of the Structural, Optical and Electrical Properties of AgInSe2 Thin Films - Khudayer, Iman Hameed; Hussein Ali, Bushra Hashem; Mustafa, Mohammed Hamid; Ibrahim, Ayser Jumah (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The Silver1Indium1Selenide (AgInSe2) (AIS) thin1films of (3001Â±20) nm thickness  have been1prepared2from the compound alloys2using thermal evaporation2 technique onto the glass2substrate at room temperature, with a deposition rate2(3Â±0.1) nm2sec-1.The2structural, optical and electrical3properties have been studied3at different annealing3temperatures (Ta=450, 550 and 650) K.The amount3or (concentration) of the elements3(Ag, In, Se) in the  prepared alloy3was verified using  an energy dispersive3x-ray spectrometer (EDS)3technology. X-ray diffraction3analysis shows that AIS alloy  prepared as (powder) and the thin films3are polycrystalline  of tetragonal3structure with preferential orientation3(112). The crystalline3size increases  as a function3of annealing temperature. The atomic force3microscope (AFM) technique  was used to examine3the  topography  and  estimate3the surface roughness, also the  average grain3size of the films. The results show3that the grain size increases3with annealing3temperature.  The optical4band gap of the films lies4in the range 1.6-1.9 eV. The films4appear to be4n-type indicating that the electrons4as a dominant charge4carrier. The electrical conductivity4increases  with a corresponding4increase in annealing4temperature.